Large magnetostrains of Ni-Mn-Ga/silicone composite containing system of oriented 5M and 7M martensitic particles. (15th January 2022) - Chiu, Wan-Ting; Sratong-on, Pimpet; Tahara, Masaki; Chernenko, Volodymyr; Hosoda, Hideki
Abstract: In view of the exponential rate of advancement in robotics technology, a composite material, which is promising for high-speed and large-strain actuation and sensing applications, has been developed in this study. Single-crystalline Ni49.9 Mn28.5 Ga21.6 (SC Ni-Mn-Ga) ferromagnetic shape memory alloy particles were fabricated from the polycrystalline Ni-Mn-Ga alloy by a well-controlled mechanical crushing. X-ray diffractions revealed a mixture of 5M- and 7M-martensitic phases in the SC Ni-Mn-Ga particles. A composite consisting of the silicone rubber and 20 vol.% of the crystallographically and spatially oriented SC Ni-Mn-Ga particles was fabricated by curing under a magnetic field and the chain-oriented structure was confirmed by a micro-computed tomography. This composite, which exhibited a magnetic field induced rubber-like behavior with a magnetostrain as high as 4.0% despite reduced filling factor, was attributed to the co-existence of the 5M- and 7M-martensitic phases. Graphical abstract: Image, graphical abstract